PTU-079 Effect of Inflammation on Liver Stiffness in Active Autoimmune Liver Disease: A Simultaneous Biopsy-Controlled Study Using Acoustic Radiation Force Impulse (ARFI) Elastography. (17th August 2016) - Sherman, DI; Fateen, W; Jagtiani Sangwaiya, M; Tadrous, P; Shorvon, P
Abstract : Introduction: ARFI elastography (virtual touch quantification, VTq™) is a well validated technique for non-invasive assessment of liver fibrosis in viral hepatitis. The interpretation of shear velocity readings in active autoimmune liver disease (AILD) may be affected by a number of factors. However, few studies have specifically examined the effect of inflammation on liver stiffness (LS) in this group. We report the results of a preliminary study in which LS and histology have been sampled simultaneously from the same region of liver tissue in a large cohort with active AILD. Methods: Our local database of 101 patients with AILD (63 autoimmune hepatitis AICH +/- overlap, 38 cholestatic-PBC or PSC) was investigated. LS estimation by ARFI was performed using a standard validated protocol by a single operator. Biopsies were performed from the same region of liver using an 18 G Biopince™ needle, immediately after LS measurement. Clinical, biochemical, ultrasonic and histopathological data were collated retrospectively. ARFI/histological variance (AHV) was defined as a difference of more than 1 Metavir or 2 Ishak stages from that predicted by ARFI, according to standard calibration. 1 Results: Sixty one ARFI + liver biopsies performed at the same session were identified out of a total of 164 ARFI and 114 liver biopsies. Patients included group 1: 37 active AICH (diagnosis/flare on therapy); group 2: 7 AICH remission; and group 3: 17 cholestatic liver disease. Co-pathology was seen in 8. Standard ARFI quality measures were validated in 93%. Mean ARFI shear velocities were significantly higher in group 1 compared with 2 and 3–2.41, 1.29 and 1.64 m/sec, respectively (p = 0.001). AHV occurred in 44.1, 28.6 and 29.4%, AHV prevalence was 41% overall, with 100% in group 1 and 88% overall reflecting overestimation of fibrosis. Across all groups, Ishak necro-inflammatory grade was strongly correlated with both ARFI shear velocity (r = 0.58, p <0.0001) and also AHV (r = 0.35, p = 0.006) by Spearman analysis. ALT showed a weaker correlation with AHV (r = 0.25, p = 0.06). Conclusion: These data show that variance between ARFI shear velocity and histology is common in active AILD, usually overestimating predicted fibrosis stage. Strong positive correlations were seen between histological inflammatory grade with both shear velocity and AHV, suggesting that inflammation is implicated in the observed increase in LS in this group. Confirmation of this association in further studies would suggest a potential role for ARFI elastography in monitoring resolution of inflammation during treatment of AILD. Reference: 1 D. Sherman, et al . J Hepatol 2014;60 (Suppl 1):S413. Disclosure of Interest: None Declared